Policy Advocacy at the Jambi City Social Service in Alleviating Poverty Through the Family Hope Program (PKH) - Dewi, Ratna; Baidawi, Ahmad (Journal of Administration, Governance, and Political Issues, 2024)
This research explores the policy advocacy role of the Jambi City Social Service in alleviating poverty through the Family Hope Program (Program Keluarga Harapan/PKH). The study aims to examine how the Social Service implements and impacts poverty alleviation efforts via PKH, particularly in targeting pre-prosperous families. Using a qualitative method, data were collected through observations, interviews, and documentation. The findings indicate that the Jambi City Social Service plays a strategic role in conducting validation and selection of PKH recipients based on poverty criteria defined by the Central Statistics Agency, focusing on housing conditions and family income. In Jelutung District, the validation team inspects whether potential recipients live in non-owned residences with minimal housing standards—such as dirt floors and tin roofs—and have household incomes under one million rupiah. Supporting evidence, including photographs, is gathered to justify eligibility. Post-validation, data are submitted to the Ministry of Social Affairs, which performs a final verification. From 50 validated families, only about 30 were approved, highlighting the strict filtering process. This study concludes that effective policy advocacy and strict validation mechanisms are essential for accurate targeting and successful implementation of PKH as a poverty alleviation strategy.